Student Smoking Behavior in the Implementation of the Smoke-Free Area Policy at SMA Negeri 1 Palu - Arwan Arwan; Firmansyah; Sadli Syam; Herman; Rasyika Nurul Fadjriah; Sendhy Krisnasari; Khairunnisaa; Mohammad Fikri (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Smoking behavior is defined as the activity of inhaling smoke from cigarettes made of rolled dried tobacco leaves that are burned and subsequently exhaled by the individual. Smoking behavior is considered a public health issue that contributes to various health problems and even death, affecting both active smokers and passive smokers who are exposed to cigarette smoke. Smoking behavior among adolescents is no longer a new phenomenon. Low self-motivation to quit smoking, along with environmental and peer influences, are factors that make it difficult for individuals to stop smoking. This study aimed to identify students’ smoking behavior in the implementation of the Smoke-Free Area policy at SMA Negeri 1 Palu. The study employed a qualitative method with a case study approach. A total of 10 informants participated in this study. Data were managed using matrix analysis techniques. The findings indicated that students’ knowledge regarding the harmful effects of smoking was relatively good. However, students’ attitudes toward peer invitations to smoke were still inadequate, as some students continued to accept such invitations. In addition, the availability of facilities and opportunities that enabled students to obtain cigarettes, such as using pocket money provided by parents or receiving cigarettes from friends, also supported smoking behavior. On the other hand, support from certain peers in the form of advice and encouragement helped male adolescents avoid smoking behavior.